Punca-punca kelewatan permohonan harta pusaka kecil : kajian kes : Pejabat Pembahagian Pusaka dan Pejabat Daerah dan Tanah di Negeri Perak - Mohd. Yusoff, Mohd. Fauzi (2004)
The problem of undistributed estate in Malaysia is becoming increasingly serious and complex. It has became a big issue that we can see through newspapers and mass media giving information about millions of ringgit of unclaimed estates and kept at the Department of National Accounts, Trustees, Employees Provident Fund (EPF) and others. Nowadays, the estate or assets that were frozen due to failures of beneficiaries to claim the funds including savings in the EPF, the savings and cooperative banks, vehicles, property such as houses and buildings, unit trusts, insurance and Takaful, investment in shares companies, trusts, intellectual property, royalties and more. At the preliminary stages, the researcher has come out with two objectives, firstly to examine the implications of the undistributed estate to the Estates Distribution Unit and secondly to examine the implications of the undistributed estate to the beneficiaries. The researcher has chosen the South Johor Estates Distribution Unit, Department of Lands and Minerals as the case study because this research is focusing on the small estate management for movable and immovable property with values not exceeding RM2 million. To achieve these objectives, the researcher had conducted interviews with the officers of South Johor Estates Distribution Unit. This study was also conducted by distributing questionnaires to respondents from beneficiaries, those who deal at the case study and the public and this also includes respondents among the officers and supporting staff in the department. Data was analyzed using SPSS version 17.0 by using the Likert scaling analysis, frequency analysis and cross tabulation analysis. The results have shown that there was a large implication from the undistributed estate to the South Johor Estates Distribution Unit, Department of Lands and Minerals and the beneficiaries of the estates. It is hoped that these findings can be used as an assessment, reference and a guideline in terms of enforcement of law in addressing this issue. Furthermore, it will also confer benefits to the parties involved. At the end of the study, suggestions have been submitted by the researcher.